Strategi Pembangunan Berkelanjutan di Era Otonomi Daerah Berbasis Partisipasi Masyarakat - R. Sabrina (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
This article describes how sustainable development strategies in the era of regional autonomy are based on community participation. The method used was a qualitative research method with a descriptive approach, data obtained through a number of journals and relevant research results as well as support from books that were connected to the focus of the study. Furthermore, the data that has been collected was then analyzed based on the problem formulation that has been determined at the beginning of this paper. The results of this study indicate that sustainable development is a problem that is the focus of community development which is carried out based on the interests and welfare of the community itself. In the era of regional autonomy, community participation will determine the sustainability of development in various sectors. Thus, community participation must be used as a benchmark for the success of development in the era of regional autonomy, but this becomes constrained when faced with political interests in the applied democratic system, so other models and strategies are needed for community participation in the era of autonomy in the context of sustainable development which becomes a stronger position.